Analisis Komunitas “Wardah Youth Ambassador Medan” Dalam Meningkatkan Brand Awareness di Kota Medan - Alya Sherin; Yusniah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
In the increasingly competitive beauty industry, building strong brand awareness is key to maintaining market relevance, especially among young consumers. This study aims to analyze the role of the Wardah Youth Ambassador (WYA) Medan community in increasing brand awareness of the halal cosmetic brand Wardah in Medan City. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results show that WYA Medan actively organizes educational and promotional activities both online and offline that are able to attract the attention of the young market. Programs such as beauty classes, social campaigns, and consistent social media content have been proven to increase brand recognition, brand recall, and top of mind achievement. Analysis of social media engagement shows that applicative content such as skincare routines has the highest engagement rate, reflecting the strength of the community's digital approach. Thus, WYA Medan plays a role as a strategic agent that strengthens Wardah's brand awareness through a community-based marketing approach that focuses on emotional closeness and participatory communication